RESPON EKSPLAN PISANG KLUTUK (Musa paradisiaca L.) TERHADAP KONSENTRASI EKSTRAK BIJI PINANG MUDA DAN AIR KELAPA MUDA SECARA IN VITRO - Zulkifli; Selvia Sutriana (UIR Press, 2019)
Nurseries play an important role in banana development. The tissue culture technique is an alternative to produce quality seeds in large quantities, uniform and produced in a short time and free of pathogens. Areca nut extract is an organic material that contains tannin and can replace bicycling used as a disinfectant in tissue culture activities. Coconut water is a food reserve that contains vitamins and growth substances, so it can stimulate germination. The purpose of the study was to examine the interaction and single response of klutuk banana explants to the concentration of areca nut extract and young coconut water in vitro. This research was carried out at the Biotechnology Laboratory, Faculty of Agriculture, the Islamic University of Riau with the planting material used Pisang Klutuk weevil with the method used in a factorial Completely Randomized Design (CRD) with 4 x 4. The first factor was seed extract Young areca nut and the second factor was Young Coconut Water. The parameters observed were the percentage of live explants, the percentage of contaminated explants, the age of shoot emergence, and the number of shoots. The observation results were analyzed statistically and continued with the further test of Honest Significant Difference (HSD) at the 5% level. It was found that the best treatment was P2K2 (20% young betel nut extract (200 ml + 800 ml distilled water) and young coconut water 20 ml/liter media), where the percentage of life was 100%, the percentage of contamination was 0%, the age of shoots appeared was 37.67 days, and the number of shoots was 5 strands.